Tożsamość człowieka z etycznego punktu widzenia - Ślipko, Tadeusz (Horyzonty Wychowania, 2017)
Taking up the subject of man’s identity from ethical point of view, the author, to begin with, explains the concept of „identity” from various points of view as presented by various scientific disciplines: psychology, marxist philosophy, christian philosophy. As a consequence, he distinguishes „essential identity”, fundamental for ethical reflections of the subject and man’s „individual identity”. Elaborating on the issue, according to christian philosophy, he defines man as a „human being”, who is the dynamic subject of his own rational activity. Then, the author deals with the problem of freedom as a category which determines his identity. Psychological freedom, the basic one, makes man reach decisions about acting or non-acting, about the choice between right and wrong, which leads to the tense ambivalence in choice. However, only moral perception of freedom makes that man, ascending in transcendental sphere, aims for perfection, modelled on the objective order of moral values rooted in rational nature. This is how human freedom assumes a form of moral freedom based on moral order full of nobleness and stability. It is also how the essence of man’s identity is expressed. The author ends with a statement that: „Closer to objective truth is the conception of man creating his own individual identity through creative moral deeds, according to their objective exemplars, rather than via the spirit of philosophical existentialism, searching for identity in the world deprived of moral signposts”.